THE CHARACTERISTIC OF RECENT SEDIMENT IN SEGARA ANAKAN LAGOON, CIAMIS REGENCY, WEST JAVA - I Wayan Lugra; Hananto Kurnio (Marine Geological Institute of Indonesia, 2009)
The high intensity of erosions at the rivers upstream which are rivermouthed into the Segara Anakan Lagoon, as sources of the materials which are causing the sedimentation on the lagoon systematically. Based on smear slide analyses and major element contents, source of the sediment which is deposited in the lagoon floor, was predicted as the volcanic products. This condition is supported by the existence of non biogenic materials such as quartz, mica, ferro-oxides, manganese oxides and tuff in the lagoon. Beside that, the existence of major elements such as SiO2 (36,6 – 51,4%) Al2O3 (13,38 – 24,70%), and Fe2O3 (8,69 – 30,6%), is particular element indicators of volcanic products. The lithology in the survey area are volcanic products such as Jampang Formation and Panutuan Formation. Jampang Formation consist of volcano breccia, tuff intercalated with lava and sandstone, claystone, napal intercalated with conglomerate. Panutuan Formation consist of sandstone, napal and tuff, Formation Members of Tuff Napalan, Panutuan Formation, which are spread on the basinal area of Citanduy, Cibeureum, and Ciseel rivers which are rivermouthed into Segara Anakan Lagoon. Key words : smear slide, major element, Segara Anakan. Intensitas erosi yang tinggi di daerah hulu sungai-sungai yang bermuara di Segara Anakan sebagai sumber material yang mengakibatkan sedimetnasi laguna secara sistematis. Sumber pasokan sedimen yang diendapkan di dasar laguna berdasarkan analisis sayatan oles, dan unsur utama mineral diperkirakan merupakan produk vulkanik yang bersifat basa. Hal ini didukung oleh terdapatnya mineral non biogenik seperti mineral kuarsa, mika, oksida besi, oksida mangan yang dijumpai tersebar secara merata, adalah produk vulkanik, berupa tuff. Disamping itu keterdapatan unsur utama mineral seperti SiO2 dengan kisaran 36,6 – 51,4%, kemudian Al2O3 dengan kisaran 13,38 – 24,70% sedangkan Fe2O3 dengan kisaran 8,69 – 30,6%, merupakan mineral khas hasil produk vulkanik yang bersifat basa. Litologi daerah penelitian merupakan produk gunungapi, seperti Formasi Jampang yang tersusun oleh breksi gunungapi tuff dengan sisipan lava, berselingan dengan batupasir, batulempung napal dengan sisipan konglomerat. Formasi Panutuan yang tersusun batupasir, napal dan tuff, Anggota Tuff Napalan formasi Panutuan, dan berada di daerah rendahan sungai Citanduy, Cibeureum, Ciseel beserta anak anak sungainya yang bermuara di Segara Anakan. Kata kunci : sayatan oles, unsur utama, Segara Anakan